A Rare Case of Clavicle Osteomyelitis in a Child and Literature Review - Elisavet-Anna Chrysochoou; Charalampos Antachopoulos; Konstantinos Badekas; Emmanuel Roilides (Case Reports in Pediatrics)
Acute clavicle osteomyelitis in children is rare representing <3% of osteomyelitis cases. We treated a 12-year-old boy who presented with acute pain in the right clavicle and high fever for 4 days. MRI showed abnormal signal in the right clavicle with periosteal reaction. Staphylococcus aureus isolated from blood was susceptible to methicillin, clindamycin, and macrolides. Clindamycin was given intravenously for 3 wks and orally for another 3 wks with no recurrence. We reviewed clavicle osteomyelitis cases in children searching PubMed English literature. From a total of 89 studies retrieved, only 6 fulfilled the criteria and were analyzed. Sixteen patients (56% female) were included with a median age of 9 yrs (range 2 wks–16 yrs). Osteomyelitis was hematogenous in most cases, with S. aureus being the most frequent cause, isolated from either blood or tissue. Symptoms included fever, swelling, and localized bone tenderness. Antimicrobial therapy lasted for 4–12 weeks (median 7.5). Three patients required drainage or curettage. Recurrence occurred in 1/16 cases (6.2%) and persistence of symptoms occurred to 2/16 cases (12.5%) reported before 90s with unknown antimicrobial susceptibility of the pathogen. Acute clavicle osteomyelitis mainly affects older children and has generally good prognosis. Staphylococcus aureus is most commonly implicated and surgery may be needed.